2004
DOI: 10.1002/pca.772
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide extraction of marigold at high pressures: comparison of analytical and pilot‐scale extraction

Abstract: The effects of pressure and co-solvent on the extraction of anti-inflammatory faradiol esters in marigold (Calendula officinalis L.) were investigated by supercritical fluid extraction at laboratory and pilot scales. Pressures higher than 300 bar and modifier (ethanol) concentrations ranging from 0 to 20% (v/v) were used at an extraction temperature of 50 degrees C. With an analytical extractor, exhaustive extraction of the drug and highest concentrations in the extracts were achieved with 0.5% ethanol at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
3
18
0
1
Order By: Relevance
“…Dichloromethane extracts contained a greater amount and variety of chemical compounds as identifiable, intensely colored bands on the HPTLC plates, in comparison to ethanol extracts. This is supported by previous work that suggests that the active antiinflammatory faradiol esters in Calendula officinalis are more soluble in less polar organic solvents such as dichloromethane [7]. Extractions using individual parts of fresh flowers (i.e.…”
Section: Evaluation Of the Extraction Proceduressupporting
confidence: 73%
See 1 more Smart Citation
“…Dichloromethane extracts contained a greater amount and variety of chemical compounds as identifiable, intensely colored bands on the HPTLC plates, in comparison to ethanol extracts. This is supported by previous work that suggests that the active antiinflammatory faradiol esters in Calendula officinalis are more soluble in less polar organic solvents such as dichloromethane [7]. Extractions using individual parts of fresh flowers (i.e.…”
Section: Evaluation Of the Extraction Proceduressupporting
confidence: 73%
“…It is commonly known as marigold, gold bloom and holligold. The anti-inflammatory and anti-oedematous properties of Calendula officinalis have been linked to the pentacyclic mono-, di-and trihydroxy triterpenoid fatty acid esters, especially the faradiol esters, faradiol 3-O-laurate, faradiol 3-O-palmitate and faradiol 3-O-myristate ( Figure 1) [5][6][7][8][9][10]. The unesterified faradiol produced by hydrolysis, has been found to have the same effect as an equimolar dose of indomethacin which is a Non-Steroidal Anti-Inflammatory Drug (NSAID) [11].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the process, a global yield of 5 % and an extract that contained 85 % faradiol of the total ester fraction were attained. One work from Baunmann et al [13] reported the SFE of marigold from a small scale (bed extraction volumes of 9×10 -6 m 3 , with temperature and pressures of 323 K and 30, 50 and 68.9 MPa, respectively, with extraction times of 90 -180 min).The global yields ranged from 5.5 % to 8.3 %, depending on the extraction pressure. The authors also studied the effect of scaling up to a pilot plant scale with bed extraction volumes of 7.0 ×10 -3 m 3 , concluding that a qualitative and quantitative improvement can be obtained by increasing the pressure and by adding a small amount of an extraction modifier, i.e.…”
Section: Sfe Technology Can Be Awarded As a Superior Extraction Technmentioning
confidence: 99%
“…The dynamic behaviour of Marigold oleoresin extraction was so far observed only for high-pressure extraction technique using liquid and supercritical carbon dioxide in order to analyse the influence of pressure and temperature on extraction yield of xanthophylls esters (Ambrogi & Egger, 1997;Baumann et al, 2004;Campos, Michielin, Danielski, & Ferreira, 2005). Since the intention of present kinetics study of Marigold extraction was to examine the isolation of free e nonesterified lutein, applicability of one step procedure comprising conventional extraction and simultaneous saponification (alkali hydrolysis) was examined.…”
Section: Introductionmentioning
confidence: 99%